Analysis of Regional Peculiarities of Strongylid (Nematoda, Strongylidae) Biodiversity in Domestic Horses in Ukraine - Kuzmina, T.A. (Вестник зоологии, 2012)
Analysis of regional peculiarities of species composition and structure of strongylid communities in domestic horses from various parts of Ukraine is presented. More than 86,000 strongylid specimens were collected using the diagnostic deworming technique from 180 horses in 10 regions (Kyivska, Kyrovogradska, Poltavska, Kharkivska, Sumska, Donetska, Ternopilska, Zakarpatska, Khersonska and AR Crimea) and identified to the species level. Thirty-three strongylid species from 12 genera were found – 26 species in the subfamily Cyathostominae and seven – in the subfamily Strongylinae. General structure of the strongylid community appeared to be multimodal. The highest biodiversity of strongylids was found in horses from Southern regions of Ukraine (29 species from 12 genera) and the lowest in Eastern regions (15 species from six genera). However, no statistically significant differences in species composition of strongylid communities in horses from various regions of Ukraine were found (p > 0.05). Comparison of strongylid biodiversity in domestic horses from Ukraine with that from others countries revealed the highest similarity of the strongylid communities from Ukraine, Czech Republic, and Poland; the lowest was in horses from South Africa and north-western Europe (France and the UK). Our results showed that the peculiarities of horse-keeping conditions influenced the biodiversity of the strongylid communities in domestic horses much more than climatic conditions in various regions. Проведен анализ региональных особенностей видового разнообразия и структуры сообществ стронгилид домашних лошадей из разных регионов Украины. Методом диагностической дегельминтизации собрано и определено до вида более 86 тысяч экз. стронгилид от 180 домашних лошадей из 10 областей (Киевской, Кировоградской, Полтавской, Харьковской, Сумской, Донецкой, Тернопольской, Закарпатской, Херсонской областей и АР Крым). Зарегистрировано 33 вида стронгилид из 12?родов — 26 видов циатостомин и 7 видов стронгилин. Обнаружена мультимодальная структура сообщества стронгилид. Наибольшее видовое разнообразие сообщества стронгилид обнаружено у лошадей из южных областей Украины (29 видов из 12 родов), наименьшее — в восточных областях (15 видов из 6 родов). Однако статистически достоверных различий в видовом разнообразии сообществ стронгилид лошадей из разных областей Украины не обнаружено (p > 0,05). При сравнении видового разнообразия сообществ стронгилид домашних лошадей Украины с таковыми из других стран мира обнаружено наибольшее сходство сообществ у лошадей Украины, Чехии и Польши. Наибольшие достоверные отличия в видовом составе сообществ обнаружены у лошадей Южной Африки, а также северо-западной Европы (Франция и Великобритания). Результаты нашей работы показывают, что особенности условий содержания домашних лошадей оказывают более сильное влияние на видовое разнообразие сообществ стронгилид, чем разница климатических условий региона.